Implementasi Peraturan Bupati Manggarai Timur Nomor 15 Tahun 2019 Tentang Percepatan Penurunan Stunting di Kelurahan Kota Ndora dan Kelurahan Rana Loba Kecamatan Borong - Victoria Desriana Meo; Saryono Yohanes; Hernimus Ratu Udju (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
This study examines the implementation of East Manggarai Regency Regulation Number 15 of 2019 regarding the acceleration of stunting reduction in Kota Ndora and Rana Loba Urban Villages, Borong District. Through a juridical-empirical approach, primary data was obtained through interviews, observations, and document studies. The results show that the implementation of the regulation is still not effective due to factors such as ineffective human resources, inadequate infrastructure, limited budget allocation, and low community participation. The study recommends improvements in training and education for human development cadres, increased budget allocation for stunted families, and a reassessment of budget allocation to ensure efficiency and effectiveness in addressing stunted families.